2007
DOI: 10.1111/j.1600-0846.2007.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive monitoring of oxidative skin stress by ultraweak photon emission (UPE)‐measurement. I: mechanisms of UPE of biological materials

Abstract: Measurement of UPE could be proven to be a highly sensitive method to assess oxidative processes in biological molecules. The reported data indicate that UPE generated by oxidation stressed skin is mainly due to non-fluorescent photon emission via Trp, whereby Trp acts as an energy receptor from other excited species of oxidation-modified amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Despite some advances in recent years [14,21] , the exact biochemical origin of chemiluminescence from human skin has yet to be determined, but has been linked to oxidation of proteins, lipids and DNA, especially from the dermis. ROS generally act on a short timescale due to their chemical reactivity and an immediate measurement is required in order to best investigate their effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some advances in recent years [14,21] , the exact biochemical origin of chemiluminescence from human skin has yet to be determined, but has been linked to oxidation of proteins, lipids and DNA, especially from the dermis. ROS generally act on a short timescale due to their chemical reactivity and an immediate measurement is required in order to best investigate their effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous chemiluminescence has been linked to oxidation of proteins, DNA and lipids [14,15] . Using ICL-S (induced chemiluminescence of human skin), UVA filter testing can be performed for sunscreen formulations in vivo independently from UVB filter content [16,17] , which is not possible with any other technique currently available (apart from the PPD method).…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable dependence of the one-dimensional photon emission on the concentration of molecular oxygen revealed the possible involvement of ROS in photon emission from the human body [32]. The proposal on the involvement of ROS in one-dimensional photon emission from human skin has been supported by the effect of topical application of exogenous oxidant (H 2 O 2 ) [27] and antioxidant (vitamin C and a-glycosylrutin) [33] on the photon emission from the hand. Based on these observations, it has been proposed that one-dimensional ultra-weak photon emission is accompanied by the formation of ROS during the oxidative metabolic processes.…”
Section: Discussionmentioning
confidence: 94%
“…7,25 It was observed that UV-radiation-induced ultraweak photon emission in the human skin showed a maximum of photon emission in the spectral range 400 to 580 nm, supporting the assumption that 3 ðC ¼ OÞ Ã is a main source of ultraweak photon emission. 7,28 In contrast, it has previously been demonstrated that UVAinduced ultraweak photon emission is in the red region of the spectrum. [30][31][32][33] In our present study, we investigated the effect of visible light and UVA radiation on ultraweak photon emission by employing a highly sensitive charge coupled device (CCD) camera and a low-noise photomultiplier tube (PMT).…”
Section: Introductionmentioning
confidence: 99%
“…23,25,27 The spectral analysis of spontaneous ultraweak photon emission from human skin has indicated that photons are spontaneously emitted mainly in the red region of the spectrum, revealing that 1 O 2 predominantly contributes to the photon emission. 28 In contrast, it has previously been demonstrated that spontaneous ultraweak photon emission is in the bluegreen region of the spectrum. [30][31][32][33] Employing immunoblotting techniques, it has recently been demonstrated that exposure of human skin to UV radiation results in the formation of C ¼ O in the human stratum corneum.…”
Section: Introductionmentioning
confidence: 99%